2015
DOI: 10.1021/ar500426g
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Oxidation Using Gold-Containing Catalysts

Abstract: Glycerol is an important byproduct of biodiesel production, and it is produced in significant amounts by transesterification of triglycerides with methanol. Due to the highly functionalized nature of glycerol, it is an important biochemical that can be utilized as a platform chemical for the production of high-added-value products. At present, research groups in academia and industry are exploring potential direct processes for the synthesis of useful potential chemicals using catalytic processes. Over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
232
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(243 citation statements)
references
References 40 publications
(79 reference statements)
5
232
0
6
Order By: Relevance
“…aldehydes, ketones or carboxylic acids) over solid catalysts is an industrially desired process and was reviewed by Mallat and Baiker in 2004 [55]. Since then numerous studies have appeared discussing the mechanistic implications of water on the product selectivity using Au-based catalysts [56][57][58][59][60]. The theme of this review, combining selective noble metal catalysts with O 2 activation by water-mediated proton transfer chemistry, was successfully followed by Davis and co-workers, who developed methods for the aqueous aerobic oxidation of glycerol to glyceric acid and other partial oxidation products over Au and Au-Pd alloy catalysts [61,62].…”
Section: Alcohol Oxidationmentioning
confidence: 99%
“…aldehydes, ketones or carboxylic acids) over solid catalysts is an industrially desired process and was reviewed by Mallat and Baiker in 2004 [55]. Since then numerous studies have appeared discussing the mechanistic implications of water on the product selectivity using Au-based catalysts [56][57][58][59][60]. The theme of this review, combining selective noble metal catalysts with O 2 activation by water-mediated proton transfer chemistry, was successfully followed by Davis and co-workers, who developed methods for the aqueous aerobic oxidation of glycerol to glyceric acid and other partial oxidation products over Au and Au-Pd alloy catalysts [61,62].…”
Section: Alcohol Oxidationmentioning
confidence: 99%
“…The gradually increasing production of biodiesel has generated a huge amount of by‐products, the major part of which is glycerol 1. It is reported that glycerol is comprised of approximately 10 wt % of the total product yield for biodiesel production2 and as such, it is projected that the demand for the consumption of glycerol will increase from 2000 kt in 2011 to 3070 kt by 2018 3. Therefore, transforming glycerol into valuable derivatives could be an effective method to increase the economic efficiency of biodiesel production.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol oxidation could produce various high-value fine chemicals [6,7], such as dihydroxyacetone (DHA), glyceric acid, glyceraldehyde, and hydroxypyruvic acid. Platinum and gold catalysts are found to be the most active among the investigated catalysts for glycerol oxidation, and carbons (active carbon and carbon nanotubes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Platinum and gold catalysts are found to be the most active among the investigated catalysts for glycerol oxidation, and carbons (active carbon and carbon nanotubes, etc.) [7][8][9] and metallic oxides (TiO 2 , Al 2 O 3 , CeO 2 , CuO, MgO, MgAl 2 O 4 , etc.) [7,[10][11][12][13][14][15][16] have been widely investigated as supports in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation